Factors Affecting Academic Administration of Schoolsunder Surat Thani Catholic Foundation - สมวงษ์ ชาติชาย; การีเวท สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this research were: 1) To study the level of the factors affecting academic administration of school, 2) To study the level of academic administration of school. 3) To study the relationship between the factors and the academic administration of school and, 4) To study the factors affecting the academic administration of school. The sample group consisted of the administrators and the teachers, totaling of 242 people determined by using the Krejcie and Morgan table (Krejcie & Morgan, 1970), Stratified random sampling was employed with simple random sampling through lottery drawing. The research instrument used was a questionnaire. The Index of Item-Objective Congruence (IOC) ranged from 0.80 to 1.00, and the reliability coefficient was 0.986. The statistics for data analysis were mean, standard deviation, Pearson’s product moment correlation coefficient and multiple regression analysis. The research findings were as follows: 1) The level of factor affecting academic administration in school by mean and standard deviation was at a high level. (x̄= 4.45, S.D.= 0.484) 2) The level of academic administration in school by mean and standard deviation was at a high level. (x̄=4.46, S.D.= 0.519) 3) The factors affecting the academic administration in school overall had a high level of positive relationship (rxy=.880) with statistical significance at .01 level with the academic administration of the school. 4) Good predictive variables of the factors affecting academic administration of school were the factor of parents and community (X3), the factor of buildings (X4) and the factor of teachers (X2). All of these were statistical significance at the .01 level. The cumulative correlation coefficient was at 0.888. The prediction of academic administration of school was 78.63 percent and could be written in a prediction equation as follows: Forecasting equations in raw score: Y = .359X4 + .315X2 + .290X3 + .161 Forecasting equations in standard score: Zy = .377ZX4 + .328ZX2 + .315ZX3